Sosialisasi untuk Mengurangi Food Waste Rumah Tangga di Wilayah Kerja Puskesmas Parung Panjang Kabupaten Bogor - Swamilaksita, Prita Dhyani; H, Harna; Suryani, Fitra; Sa'pang, Mertien; Kusumaningtiar, Devi Angeliana (PT.Mantaya Idea Batara, 2023)
Food waste (FW) consists of organic-rich resources for consumption that are then discarded, wasted, decomposed, or damaged. The impacts of FW from several aspects have been demonstrated, such as the 1.3 billion tons of food wasted per year that costs the global economy and adds to greenhouse gas emissions. In addition, there is the impact of famine if FW is not addressed. However, food waste is the result of poor food handling habits and behaviors such as planning, shopping, cooking, eating, storing, and handling food waste. The method of community service is lecture/counseling, accompanied by discussion and questions and answers. This community service was carried out in August-October 2022 at the Parung Panjang Health Center Working Area, Bogor Regency. The results of the service, we get pre-test and post- test presentations are not different (there has been no increase in knowledge after socialization). FW in the household is still a common thing to do so that socialization needs to be carried out continuously along with assistance so that knowledge increases accompanied by changes in behavior for the better.